Photophobia as a Presenting Feature in Adie’s Tonic Pupil - Parajuli, S.; Sharma, S.; Shrestha, R.; Chapagain, S.; Singh, P.; Shrestha, R. (Kathmandu University Medical Journal, 2022)
A 34 years old female presented with complains of photophobia since 6-7 months. On examination, she had anisocoria of 4 mm in room light which increased in bright light. The left pupil was dilated and unresponsive to direct and indirect light stimuli. It did however, constrict slowly on near fixation followed by slow re-dilatation on distance fixation. A diagnosis of Adie’s tonic pupil was made since left pupil constricted with instillation of dilute pilocarpine 0.1%. Her symptoms of photophobia and blurred vision immediately resolved. Photochromatic glasses and dilute pilocarpine 0.1% three times a day were prescribed. Prompt symptomatic relief of photophobia and blurred vision was observed.